Effect of inhaled beclomethasone dipropionate on saliva cortisol concentrations. Issue 6 (June 1984) - Williams, H; Read, G F; Verrier-Jones, E R; Hughes, I A
Abstract : Serial saliva cortisol measurements were used to assess pituitary-adrenal function in a group of asthmatic children treated with beclomethasone dipropionate (400 micrograms daily). Asthmatic children who were not being treated with steroids and normal children were also studied for comparison. A diurnal cortisol rhythm was observed in all three groups. Early morning cortisol concentrations were significantly higher in the group treated with beclomethasone dipropionate than in the normal children; this may indicate a stress induced response to decreased morning peak expiratory flow. In both groups, plasma and salivary cortisol responses after adrenocorticotrophic hormone stimulation test were normal but peak cortisol concentrations showed a 7 fold increase over basal values in saliva compared with a three fold increase in plasma. Beclomethasone dipropionate does not suppress pituitary-adrenal function in children when used in recommended doses. Serial measurement of the salivary cortisol concentration is a simple, safe, and sensitive method for the routine monitoring of adrenal function in children treated with this steroid. Monitoring may be supplemented with an assessment of the adrenal response to adrenocorticotrophic hormone stimulation, if necessary.